2020
DOI: 10.1177/2325958220935264
|View full text |Cite
|
Sign up to set email alerts
|

Training Exposure and Self-Rated Competence among HIV Care Providers Working with Adolescents in Kenya

Abstract: Lack of health care worker (HCW) training is a barrier to implementing youth-friendly services. We examined training coverage and self-reported competence, defined as knowledge, abilities, and attitudes, of HCWs caring for adolescents living with HIV (ALWH) in Kenya. Surveys were conducted with 24 managers and 142 HCWs. Competence measures were guided by expert input and Kalamazoo II Consensus items. Health care workers had a median of 3 (interquartile range [IQR]: 1-6) years of experience working with ALWH, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Differences in results can be accounted by higher education level and homogenous group of counselors against a heterogeneous group of health workers in the Kenyan study. [12] In the Ugandan study perceived self-efficacy was high (mean 7.6 on a tenpoint response scale), which compares favorably with current study. In both studies higher self-confidence rating was for items that had clearly defined procedures like maintaining confidentiality in current study and counseling people living with HIV (PLHIV) to start ART early, in the comparator study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Differences in results can be accounted by higher education level and homogenous group of counselors against a heterogeneous group of health workers in the Kenyan study. [12] In the Ugandan study perceived self-efficacy was high (mean 7.6 on a tenpoint response scale), which compares favorably with current study. In both studies higher self-confidence rating was for items that had clearly defined procedures like maintaining confidentiality in current study and counseling people living with HIV (PLHIV) to start ART early, in the comparator study.…”
Section: Discussionsupporting
confidence: 65%
“…[11] Mean age also agreed with a study on adolescent HIV providers of Kenya, however participants of our study had higher education levels and service experience as only 27.5% of respondents in the Kenyan study started a degree program and had median service experience of four years. [12] In the Kenyan study the median competence score was high, and it was statistically significant for training and years of experience in adolescent HIV care. Our study too reported high rating but it did not vary with type of training or years of service experience and education level emerged as the most important predictor in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Self-rated competence in interacting with AYA was evaluated before training and immediately post-training using Likert scale items (1 = strongly disagree to 5 = strongly agree ). 19 The self-rated competence domains in caring for AYA included aspects on HCW knowledge (understanding issues ALHIV face, feeling sufficiently trained to offer AYFS), skills (effective communication, sufficient clinical and emotional skills), abilities (confidence in providing care) and attitudes (empathy, comfort interacting with ALHIV). In addition, HCWs rated case difficulty in communication and medical decision-making (1 = very challenging to 5 = very easy ), realism and relevance of each SP encounter (1 = very irrelevant/ unrealistic to 5 = very relevant/ realistic ).…”
Section: Methodsmentioning
confidence: 99%
“…Participation in the surveys was 100%. Surveys assessed sociodemographics and self-reported competence and training in caring for AYALWH, as described previously (Karman et al, 2020). Due to high turnover in the health care workforce, we did not assume that a health facility offering a training meant that all providers had received training.…”
Section: Data Collectionmentioning
confidence: 99%
“…Forty-two percent of facilities (n 5 10) currently had at least one provider with AYALWH training. We provide additional HCW characteristics elsewhere (Karman et al, 2020).…”
Section: Facility-level Correlates Of Viral Suppressionmentioning
confidence: 99%